Pengaruh Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Inspektorat Provinsi Sumatera Utara - Hutabarat, Lamminar; Telaumbanua, Meli (Cattleya Darmaya Fortuna, 2025)
This study aims to determine the influence of the work environment and organizational culture partially and simultaneously on the performance of employees of the Inspectorate of North Sumatra province. This research is a quantitative descriptive research with instrument questionnaire conducted with a population of all employees Inspectorate of North Sumatra Province. Sampling with Slovin formula samples obtained a sample of 62 people. The results of multiple linear regression equation is: Y = 23,436 + 0,401X1 + 0,216X2 the value of the work environment tcount coefficient is 2.474 and the ttable value is 2.000, so that tcount (2.474) > ttable (2.000 and 0.016 < 0.05, the value of the organizational culture tcount coefficient is 2.312 and the ttable value is 2.000, the so that tcount (2.312 > ttable (2.000) and 0.024 < 0.05, the value of the work environment and organizational culture Fcount coefficient is 20.158 and the value of Ftable is 2.76, so that 20.158 > 2.76 and 0.000 < 0.05. RSquare value of 0.700 or R2 x 100% of 70.00%, meaning that the independent variable of the study contributed greatly to explain the performance of employees of the Inspectorate of North Sumatra province by 70.00% while the remaining 30.00% influenced by other factors. Conclusion of the study the work environment and organizational culture partially and simultaneously significantly affect the performance of employees of the Inspectorate of North Sumatra Province.